A influ??ncia da atividade f??sica no controle auton??mico da frequ??ncia card??aca em mulheres com diferentes escores de depress??o - Tonello, La??s (2014)
Mental disorders affect more than 450 million people worldwide. It is estimated that by 2030 depression will be the most common disease in the world. Depression negatively influences autonomic nervous system control. Given the uncontrolled growth of this disease and potential risks, some studies pointed out the importance of exercise and physical activity for prevention and treatment of depression. Thus, this study aims to investigate the relationship between autonomic control, depression, physical activity and aerobic fitness in young women. The study included 51 women employed at Catholic University of Brasilia (UCB). The following evaluations were performed: anamnesis, resting electrocardiogram, body composition, submaximal cycle ergometer test, aerobic fitness test, heart rate variability (HRV) analysis, a questionnaire to assess the level of physical activity and depressive symptoms, and the assessment of physical activity levels through accelerometry. The results of this study demonstrated significant correlations between depression scores and: maximum oxygen uptake (VO2max) (r= -462, p= 0.023), and body fat percentage (r= 514, p= 0.032) and body mass index (r= 439 p= 0,032). However, there were some moderate correlations between heart rate recovery and some indices of physical activity. This study concluded that exercise and habitual physical activity are adjuncts to control of depression scores, due to the importance they play in improved levels of cardiorespiratory fitness, percentage body fat and body mass index.